Organocatalytic enantioselective γ-aminoalkylation of unsaturated ester : access to pipecolic acid derivatives - Xu, Jianfeng (2014)
The direct γ-carbon functionalization of α,β-unsaturated esters via N-Heterocyclic Carbene (NHC) catalysis is disclosed. This catalytically generated nucleophilic γ-carbon undergoes highly enantioselective additions to hydrazones. The resulting δ-lactam products can be readily transformed to optically enriched pipecolic acid derivatives.